Teori Dalil Hukum Hadhanah - Rachmat Husein Rambe; Mhd. Amar Adly; Heri Firmansyah (Student Research Journal, 2025)
This research is research on custody rights or hadhanah for underage children, child custody or hadhanah is one of the problems that arises when a husband and wife divorce, especially those who already have one or more children. , hadhanah is the task of looking after or caring for babies/small children who are not yet able to look after and regulate themselves. Receiving care and education is the right of every child from both parents. The child's parents are the ones who are more important in carrying out this task, as long as both of them have the ability to do so. In terms of custody or hadhanah of children who are not yet 12 years old, it should be given to a mother in accordance with what is regulated in Article 105 of the Compilation of Islamic Law which states that custody or hadhanah of children who are not yet 12 years old is the right of a mother. This research uses research methods Normative juridical, normative juridical, namely legal research carried out by examining library materials and using research approach models in legal researchers including legal approaches - Islamic law. The data collection method used is library data obtained through library research sourced from Islamic law, books, official documents, publications and research results. The primary data source was obtained by reading literature related to the discussion of hadhanah. The results of this research. The fuqoha agreed that hadhanah started from the birth of the mahdhun until the mumayyiz of the mahdhun, however they differed in their opinions regarding when the hadhanah ended after mumayyiz.